ASPECTS OF ESTERIFICATION PROCESS OF GLYCEROL-CONTAINING WASTE FROM BIODIESEL PRODUCTION FOR OBTAINING OF PLASTICIZING COMPOSITIONS - S. P. Safronov; E. L. Krasnykh; S. V. Levanova (Тонкие химические технологии)
Kinetics of catalytic esterification of glycerol with butanoic acid on model systems was studied. Reaction orders for the reactants (butanoic acid and glycerol) were determined. They are close to 1.It was shown that the reaction order with respect to the catalyst - orthophosphoric acid - in regions where its concentration is above 0.1 mol/l is equal to zero. The estimated value of activation energy is 51.9± 8.0 kJ/mol. The results of the experiment can be used to create an industrial technological process for the synthesis of glycerol tributyrate. This compound can be used as an alternative non-phthalate plasticizer for articles made of PVC. The obtained kinetic model was validated on glycerol-containing waste of the biodiesel synthesis from renewable raw materials. The recycling of the by-product in the biofuel production with obtaining plasticizing compositions for the polymer industry can be developed on the basis of the studies.